Analysis of Hyperthermia Effect on Peripheral Blood Natural Killer Cell Cytotoxicity against SW-872 Cell Line: - Atashzar, Mohammad Reza; Jalili, Sajad (Galen Medical Journal, 2015)
Background: Natural killer (NK) cells are a type of cytotoxic lymphocyte. It is revealed that hyperthermia which is used in cancer treatment, increases natural killer cell activity. In this study, our aim was to analyze effects of in-vitro hyperthermia on human Natural Killer cytotoxicity against SW-872 cell line. Materials and Methods: In this study, we used SW-872 liposarcoma cell line as a target cell. Peripheral blood NK cells were isolated from normal individuals by MACS. NK cells were treated at 39°C for 1hr .The expression of CD69 on the surface of NK cells was examined by flow cytometry at different time points including 0, 6 and 12 hrs. NK cell cytotoxicity was measured by LDH assay 12hrs after co-culture with SW-872. The results were compared to the conditions that both NK cells and SW-872 cells were heat treated at 39°C for 12hrs. Results: Our results revealed that cell killing activity of NK cells treated with heating alone was increased 6hrs after heat treatment at 39°C compared with heat-treated NK-target cells co-culture. While in heat-treated NK-target cells co-culture the maximum cytotoxicity was observed 12hrs after heat treatment at 39°C. Conclusion: These results showed that thermotherapy could be a feasible method to stimulate immune response against tumor cells. [GMJ. 2015;4(3):75-81]